Potential for application of feed additives encapsulation technology in animal nutrition : Potencijal za primjenu tehnologije inkapsulacije dodataka hrani u hranidbi životinja - Kolar, Sara (Array, 2021)
Demands for higher production and consumer demand for healthier food have encouraged intensive research for alternative animal growth promoters in recent years. Research trends are focused on the development of new products enriched with feed additives to improve animal health and enhancing production. Many of these compounds are unstable in the presence of light, air, water, or high temperatures and need to be protected during processing, storage, and application. By encapsulatied in microparticles, feed additives are protected from harmful external influences, and their stability and functionality are not diminished. Microencapsulation technology is used to protect payload and improve bioavailability by controlled and targeted delivery to the digestive tract. It is particularly suitable for the addition of feed additives in ruminant’s nutrition, because the correct choice of microparticle material allows the release of the feed additives in the small intestine, and not in the rumen. With proper use, microparticle formulations are an effective tool in animal nutrition that delivers nutrients and/or drugs to a specific site at the desired rate. The paper summarizes laboratory studies on the application of microencapsulation technology in feeding ruminants and monogastric animals. Numerous results of the application of encapsulated feed additives have shown a positive effect on animal health, increased productivity without negative effects on the final product, and environmental protection.